Penentuan Nilai Kalor Briket Dengan Memvariasikan Berbagai Bahan Baku - Samsinar Samsinar; Asri Saleh; Waode Rustiah (Al-Kimia, 2016)
Limitations of the availability of non-renewable energy sources. Cocoa shell waste and sawdust widespread everywhere and can be used as an alternative energy source that is to cultivate and make fuel, one of which briquetting. The composition of the material that is (90: 10 75: 25 and 50: 50). After mixing the briquettes are printed using a printer briquettes. From this study, the best calorific value contained in the ratio of sawdust 90: Water Hyacinth 10 is 6223.20 cal/g, the ratio of sawdust 90: 10 cocoa skin is 5953.72 cal / g and Leather Cocoa 90 : Water Hyacinth 10 ie 6066, 09 cal/g. The best density value in comparison sawdust: cocoa skin (75:25) ie 1.05 kg/cm3. Best values compressive strength in comparison cocoa skin: water hyacinth (50:50) ie 2.32 kg/cm3. Best water content ratio of sawdust : water hyacinth (90 : 10) ie 3. 89% ash content. Value best comparison Leather cocoa : water hyacinth (90 : 10) is 0.66%. Volatile matter best value comparison cocoa skin: water hyacinth (90:10) ie 13.1%. The best comparison value of fixed carbon sawdust: cocoa skin (90 :10) is 62,34 %.